Types of governance in education: a quantitative analysis - Michael Windzio; Reinhold Sackmann; Kerstin Martens (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2005)
This study creates a typology of education systems. It uses empirical analysis to deter-mine six types of education governance on the basis of various factors such as the de-gree of state involvement or funding sources, and structural differences of average time spent on homework or the degree of support for low achievers. It reveals differences in output among these types as measured by student performance, and relative equality of performance. The typology reflects similarities in governance of education among groups of countries, and indicates that common geography and history may be more of a linking factor than expected in a globalized world.
Keywords: 370; Bildungswesen; Vergleich; Bildungsniveau; Schätzung; Welt; Governance-Ansatz